Trends in Measuring Instrument Transformers for Gas-Insulated Switchgears: A Review - Dong-Eon Kim; Gyeong-Yeol Lee; Gyung-Suk Kil; Sung-Wook Kim (Energies, 2024)
Voltage and current measurements in high-voltage substations are fundamental for stable operation. Conventional instrument transformers (ITs) face challenges in gas-insulated switchgears (GISs), such as size, weight, accuracy limitations, and behavioral instability at abnormal voltages and currents. Non-conventional instrument transformers (NCITs) have emerged to address these issues, complying with International Electrotechnical Commission (IEC) standards and providing millivolt-level signals, enabling downsizing of GIS bays. The transition to digital substations, as mandated by IEC 61850-9-2, requires a shift from the conventional 110 V/5 A outputs to levels ranging from millivolts to volts. Electronic instrument transformers (EITs), compliant with the IEC 60044-7 and 8 standards, offer alternatives to conventional ITs with smaller sizes and wider frequency ranges. However, issues remain with EITs, including limited adoption, the necessity of separate power sources, and susceptibility to electromagnetic interference. Recent standards, transitioning to IEC 61869, focus on low-power instrument transformers (LPITs). Low-power voltage transformers (LPVTs) and low-power current transformers (LPCTs), designed with passive components, present potential solutions by directly connecting to merging units (MUs) for digital signal transmission. This review outlines the current status of various IT standards, covering conventional ITs, EITs based on IEC 60044-7 and 8, and LPITs based on IEC 61869-10 and 11. Advancements in sensor technology relevant to these standards are also explored. The paper provides insights into the evolving landscape of instrument transformers, addressing challenges and offering potential pathways for future developments in digital substations.